Bioresorbable collagen materials in surgery: 50 years of success - A. L. Fayzullin; A. B. Shekhter; L. P. Istranov; E. V. Istranova; T. G. Rudenko; A. E. Guller; R. K. Aboyants; P. S. Timashev; D. V. Butnaru (Сеченовский вестник, 2020)
Collagen materials are widely applied in medicine due to optimal handling characteristics, biocompatibility, controlled biodegradation, the ability to form complexes with drugs and facilitate regeneration. Researchers from Sechenov University developed, studied in experiments and introduced into medicine a variety of materials based on collagen — a protein of connective tissue. At the same time, new collagen materials were launched into clinical practice abroad. In this review of Russian and world literature, we described how scientific and applied studies of collagen materials developed over time and tried to illustrate the current state and trends of collagen application for a variety of medical purposes — from hemostatic sponges to tissue-engineered constructs. The range of available collagen-based medical products and the emergence of new collagen materials indicate the keen interest in this biomaterial from the medical community and the potential of future discoveries.